ASSILESSURENG AND ASSIJINGENG: THE CONCEPT OF RELIGIOUS MODERATION TOMANURUNGE RI BACUKIKI - Faisal Bachrong; Abd. Karim (Balai Penelitian dan Pengembangan Agama Makassar, 2022)
Religious Moderation is a concept that will bring peace to society. Religious moderation can be an instrument to prevent conflict and even solve social problems in society. Social problems often occur because society is very heterogeneous. Differences in ethnicity, race, religion, and culture are often social problems born of this heterogeneity. However, conflicts can be avoided by using moderate tools. One of them is using local wisdom as a unifying tool for the community. In addition, the values of religious moderation can be used to shape civil society. This article examines the values of religious moderation in the concepts of Assilessureng and Assijigeng initiated by Tomanurunge ri Bacukiki La Bangenge. Thus, the collaboration between local values and religious moderation forms a frame to limit conflicts in society. This article uses a qualitative method. Data were obtained by tracing local manuscripts and interviews with the community.